Computer control of batch process plant (plant investigation) / Mohd Fareh Mohamed Zaid - Mohamed Zaid, Mohd Fareh (1995)
This project looks up mostly in which more enhanced computer control can be provided in the batch process plant . The competitive pressures in batch processing plant production and difficulties in planning and control all call for improved design of batch plants and provide an incentive for application of computer-aided methods. The selected plant is a Non-interacting Liquid Level Control of Three Tank System (High Order Lag Process) where commonly used, in plant system in process industries. The plant system is simulated by using stepper motor where the motion or rotation can be controlled through the compatible stepper driver and logic circuit This project successfully gives the understanding of batch process plant especially where load (printer plotter) is moved in linear motion as a piston valve motion in the real plant.